Acta Mechanica Sinica - Suo, Zhigang; Lu, Tian Jian.; Shyy, Wei.; SpringerLink (Online service) (Beijing : The Chinese Society of Theoretical and Applied Mechanics; Institute of Mechanics, Chinese Academy of Sciences : Imprint: The Chinese Society of Theoretical and Applied Mechanics; Institute of Mechanics, Chinese Academy of Sciences, co-published with Springer.)
Founded in 1985, Acta Mechanica Sinica is an international journal sponsored by the Chinese Society of Theoretical and Applied Mechanics. It welcomes and records high-quality original papers in all aspects of mechanics and mechanical sciences from contributors throughout the world. The journal also serves as an effective tool for promoting scientific exchange between Chinese scientists living in China and those overseas. The journal aims to report recent developments in mechanics and other related fields of research. It covers all disciplines in the field of theoretical and applied mechanics -- including not only the classical subdivisions such as solid and fluid mechanics, but also the recently emerging areas such as biomechanics and nanomechanics. It explores analytical, computational and experimental progresses in all areas of mechanics. The journal also encourages research in interdisciplinary subjects, and serves as a bridge between mechanics and other branches of engineering and sciences. The journal publishes review articles, research papers, notes, experimental techniques, scientific events and other special topics of general interest.
Keywords: Continuum physics; Computational intelligence; Mechanics; Mechanics, Applied; Fluid mechanics; Theoretical and Applied Mechanics; Classical and Continuum Physics; Engineering Fluid Dynamics; Computational Intelligence